2019
DOI: 10.1007/s40778-019-0153-0
|View full text |Cite
|
Sign up to set email alerts
|

Recasting the Cancer Stem Cell Hypothesis: Unification Using a Continuum Model of Microenvironmental Forces

Abstract: Purpose of review: Here, we identify shortcomings of standard compartment-based mathematical models of cancer stem-cells, and propose a continuous formalism which includes the tumor microenvironment. Recent findings: Stem-cell models of tumor growth have provided explanations for various phenomena in oncology including, metastasis, drug-and radio-resistance, and functional heterogeneity in the face of genetic homogeneity. While some of the newer models allow for plasticity, or de-differentiation, there is no c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 66 publications
1
14
0
1
Order By: Relevance
“…ERK/MAPK is upregulated in many human cancers [1][2][3][4] , though its primary role in embryonic stem cells centers on differentiation [7][8][9][10] . Importantly, tumours are heterogeneous and only cancer stem cells generate a new tumour upon transplantation 62,63 . The bulk of the tumour therefore likely consists of the progeny of cancer stem cells, which are in various states of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…ERK/MAPK is upregulated in many human cancers [1][2][3][4] , though its primary role in embryonic stem cells centers on differentiation [7][8][9][10] . Importantly, tumours are heterogeneous and only cancer stem cells generate a new tumour upon transplantation 62,63 . The bulk of the tumour therefore likely consists of the progeny of cancer stem cells, which are in various states of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Another intensively debated subject in cancer research is the existence of "cancer stem cells" (CSCs) ( Fig. 5B; reviewed by Kreso and Dick 2014;Batlle and Clevers 2017;Scott et al 2019). Akin to the stem cells that constitute a fraction of different adult organs, tumors have also been suggested to possess CSCs that can self-renew and generate cells for tumor growth and malignancy (Beck and Blanpain 2013).…”
Section: Lineage Tracing In Cancer Researchmentioning
confidence: 99%
“…The identification of CSCs had inspired newer strategies of cancer therapies aiming at their elimination. Nevertheless, growing evidences indicate that both CSC and non-CSC populations within a tumor might be plastic, and their tumorigenic potential may be altered by the tumor microenvironment (for reviews, see Batlle and Clevers 2017;Scott et al 2019). In support of this idea, it has been shown that in intestinal tumors, epithelial non-stem cells can dedifferentiate into tumor-initiating cells (Schwitalla et al 2013).…”
Section: Lineage Tracing In Cancer Researchmentioning
confidence: 99%
“…The CSCH provides a conceptual framework by which to understand many different aspects of cancer progression, including: the occurrence of functional heterogeneity despite genetically identical states [2][3][4] ; resistance to chemotherapy 5,6 and radiotherapy [7][8][9] ; recurrence 10 ; and metastasis 11 . Despite its popularity, the CSCH has been the subject of continual debate and modification in order to maintain compatibility with experimental observations [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%